IMPLEMENTASI PROGRAM PELAYANAN KESEHATANPEDULI REMAJA (PKPR) DI PUSEKSMAS SENAPELAN KECAMATAN SENAPELAN KOTA PEKANBARU - Asmariva, Hielda; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study describes the implementation of health care programs caring teenagers (PKPR). Study is motivated by various problems that teens who increased cases of HIV-AIDS, drugs, and sexual freedom among young people, resulting in backed up by the latest regulations of article 36 of Law No. 136 and 137 of 2009 on implementing health programs to the youth-specific KIE method called PKPR services.Adolescent health care program is a health service to young people through special treatment tailored to the desires, tastes and needs of adolescents. This study uses the theory of implementation Merilee Grindle who saw the successful implementation of the contents of the policy and the policy environment.This study used a qualitative approach to data collection is done descriptive. Technic type circuitry observation, interview and documentation. Meanwhile, the technical validity of the data that researchers use is triangulasi source. Choosy informants conducted by using purposive sampling.The process data analysis was conducted using content analysis Based on the research that has been done, the researchers conclude that the implementation of the program by using the theory PKPR Marille Grindel that researchers do that in the implementation of the health center program doing three services is services preventive, promotive and rehabilitative services. As well as the lack of good cooperation between the various parties associated with the implementation of the program.Which is a constraint in the implementation of health care services in health centers teenager Senapelan namely the lack of funds available, socialization is not optimal, infrastructure is inadequate to support the program.Keywords: Policy Implementation, Health Services, and Program PKPR